Relación entre la representación del espacio en el dibujo espontáneo y la inteligencia - Majluf, Alegría (1990)
Two ordinal scales to assess cbildren's drawings are presented. The scales were administered to a sample of 120 cbildren divided in three age groups (4 1/2, 6 and 7 1/2) from both genders and two socioeconomic levels. Results showed a significant correlation between the ability to organize space and Piaget's level of operatory lhinking. Significant differences are observed according to age and socioeconomic level.